THE ARCHITECTURE OF SECURITY AND BROADBAND WIRELESS ACCESS 3.3 GHz DEVELOPMENT PLANNING [ Case Study at TANJUNG MAS RAYA Housing ] - Purwanto, Imam (Universitas Gunadarma, 2009)
Along with the advancement of Internet technology, currently launched Broadband Wireless Access (BWA). This technology is very popular in residencial area. In this research, implementation of BWA in Tanjung Mas Raya Estate will be explained. The concept used in this case study is RT/RW Net, which is implemented using wireless technology in the frequency of 3.3 GHz. This system will be used as communication forum between houses, such as information exchange, expressing opinion, online polling via email, chat and web portal. In the future, the system can also be used for Voice Over IP (VoIP) so that voice communication among houses will be free of charge.Keyword(s): BWA, Network, RT/RW NetSubject Description : C.2.Computer Communication Networks | C.2.0.General | Data Communications